PENGEMBANGAN MODUL AJAR BERBASIS BOOKLET DI SMP NEGERI 3 MANDREHE - GULO, NESTIN WANTALENTA; ZEGA, NOVELINA ANDRIANI; GULO, HARDIKUPATU; WARUWU, TOROZIDUHU (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
This research was motivated by the teaching materials used only coming from one source and the minimal use of teaching modules due to teacher limitations in designing the latest teaching modules. The objectives of conducting the research are: (1) To find out the feasibility of presenting booklet-based teaching modules at SMP Negeri 3 Mandrehe, (2) To know the response of students to booklet-based teaching modules at SMP Negeri 3 Mandrehe, (3) To know the effectiveness of booklet-based teaching modules in Mandrehe 3 Public Middle School. This research uses the ADDIE development model design which consists of five stages, namely: (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation (evaluation). The research location is at SMP Negeri 3 Mandrehe. The research population is class VIII students in the odd semester of the 2024/2025 academic year. Research result: (1) The percentage of presentation feasibility by the first material expert is 84,72%, the percentage is valid, by the second material expert the percentage is 81,94% the criteria are valid, by the linguist the percentage is 88,46% the criteria are valid, and by the design expert the percentage is 82,29% the criteria are valid. (2) The students' response to booklet-based teaching module products in individual tests obtained an average percentage of 72,22% for practical criteria, in small group trials the percentage was 79,67% for practical criteria, and in field tests the percentage was 88,53% for criteria very practical. (3) The effectiveness of student learning outcomes through the development of booklet-based teaching module products obtained a percentage of student learning completeness, namely 84,62% with very high criteria. According to the research results, it can be concluded that the development of booklet-based teaching modules is able to have a positive impact on improving student learning outcomes. ABSTRAKPenelitian ini dilatarbelakangi oleh bahan ajar yang digunakan hanya berasal dari satu sumber dan minimnya penggunaan modul ajar akibat keterbatasan guru dalam mendesain modul ajar terbaru. Tujuan pelaksanaan penelitian, yaitu: (1) Mengetahui kelayakan penyajian modul ajar berbasis booklet di SMP Negeri 3 Mandrehe, (2) Mengetahui respon peserta didik terhadap modul ajar berbasis booklet di SMP Negeri 3 Mandrehe, (3) Mengetahui efektivitas modul ajar berbasis booklet di SMP Negeri 3 Mandrehe. Penelitian ini menggunakan desain model pengembangan ADDIE yang terdiri dari lima tahap yaitu: (1) Analisis (analyze), (2) Perancangan (design), (3) Pengembangan (development), (4) Implementasi (implementation), dan (5) Evaluasi (evaluation). Lokasi penelitian yaitu di SMP Negeri 3 Mandrehe. Populasi penelitian yaitu peserta didik kelas VIII semester ganjil Tahun Pelajaran 2024/2025. Hasil penelitian: (1) Kelayakan penyajian oleh ahli materi pertama persentasenya yaitu 84,72% kriterianya valid, oleh ahli materi kedua persentasenya yaitu 81,94% kriterianya valid, oleh ahli bahasa persentasenya yaitu 88,46% kriterianya valid, dan oleh ahli desain persentasenya yaitu 82,29% kriterianya valid. (2) Respon peserta didik terhadap produk modul ajar berbasis booklet pada uji perseorangan diperoleh rata-rata persentasenya yaitu 72,22% kriterianya praktis, pada uji coba kelompok kecil persentasenya yaitu 79,67% kriterianya praktis, dan pada uji lapangan persentasenya yaitu 88,53% kriterianya sangat praktis. (3) Efektivitas hasil belajar peserta didik melalui pengembangan produk modul ajar berbasis booklet diperoleh persentase ketuntasan belajar peserta didik yaitu 84,62% dengan kriteria sangat tinggi. Sesuai hasil penelitian, dapat disimpulkan bahwa pengembangan modul ajar berbasis booklet mampu memberikan dampak positif terhadap peningkatan hasil belajar peserta didik.